Simultaneous separation, clean-up and analysis of musty odorous compounds in wines by on-line coupling of a pervaporation unit to gas chromatography–tandem mass spectrometry - Gómez-Ariza, J.L; Garcı́a-Barrera, T; Lorenzo, F (Analytica chimica acta, 2004)
A procedure for fast, reliable and precise analysis of 2,4,6-trichloroanisole (TCA) and other anisoles [2,6-dichloroanisole (DCA) and 2,4,6-tribomoanisole (TBA)] in cork-tainted wines has been performed. The method is based on compounds separation by pervaporation (PV) and later on-line clean-up, using a Carbofrit packed liner (CPL) fitted to the gas chromatograph–mass spectrometer injector (PV–CPL–GC–MS). Detection limit was about 54 pg for TCA (5 ng l −1 when aliquots of 10 ml were used in the analysis). These results were comparable with those obtained from the coupling pervaporation solid-phase cryogenic trap–thermal desorption GC–MS (PV–CT–TD–GC–MS) and solid-phase microextraction gas chromatography. Precision of PV–CPL–GC–MS, expressed as relative standard deviation, was 5.2, 2.0 and 6.2% for DCA, TCA and TBA, respectively. Linear range of calibration curves ranged from quantification limit to 2 ng for all the anisoles. In addition, the method based on the PV–CPL–GC–MS coupling was more rapid and reliable than that using PV–CT–TD–GC–MS, due to the one-step direct on-line introduction of analytes from the PV unit to the GC–MS system facilitated by CPL, which increases the analysis precision and sample throughput.